Proceso atención de enfermería en paciente 28 años con apendicitis aguda. - Ochoa Centeno, Joselyne Lisette (2021)
The present clinical case belongs to a 28-year-old female patient admitted to the emergency area of the hospital unit accompanied by a family member, conscious, oriented in time, space and person presenting a clinical picture characterized by initial pain at the level of the region of the hypogastrium that posteriorly radiates to the region of the right iliac fossa, accompanied by emesis, nausea, malaise, irritability, hyperthermia of 39.5 ° C, heart rate 110x´, respiratory rate 22x´, oxygen saturation 99% and blood pressure Arterial 124/62 mmHg, followed by a cephalocaudal evaluation and Marjory Gordon's functional patterns, finding other alterations in the patient pale fascie, hot to the touch, diaphoresis, discomfort when walking in her right limb, which hinders her daily activities, she cannot reconcile sleep, sleeps short periods due to the ailments presented, Eva's scale of pain at 9, restless and distressed due to mani Clinical manifestations present, in addition to performing complementary examinations providing a definitive diagnosis of acute appendicitis, nursing interventions are created and provided applying the theorizing of the 14 needs of Virginia Henderson thus avoiding complications, initially it is restricted orally due to possible surgical intervention, it is canalizes peripheral intravenous route, administration of medication according to medical indications, perform fluid balance, thermal curve, monitoring of vital signs and other nursing care to achieve independence.